De Novo Renal Cell Carcinoma in a Kidney Allograft 20 Years after Transplant - Masataka Banshodani; Hideki Kawanishi; Seiji Marubayashi; Sadanori Shintaku; Misaki Moriishi; Fumio Shimamoto; Shinichiro Tsuchiya; Kiyohiko Dohi; Hideki Ohdan (Case Reports in Transplantation)
Renal cell carcinoma (RCC) in a kidney allograft is rare. We report the successful diagnosis and treatment of a de novo RCC in a nonfunctioning kidney transplant 20 years after engraftment. A 54-year-old man received a kidney transplant from his mother when he was 34 years old. After 10 years, chronic rejection resulted in graft failure, and the patient became hemodialysis-dependent. Intravenous contrast-enhanced computed tomography (CT) for the evaluation of gastrointestinal symptoms revealed a solid 13 mm tumor in the kidney graft. The tumor was confirmed on ultrasound examination. This tumor had not been detected on a surveillance noncontrast CT scan. Needle biopsy showed that the tumor was an RCC. Allograft nephrectomy was performed. Pathological examination showed that the tumor was a Fuhrman Grade 2 RCC. XY-fluorescence hybridization analysis of the RCC showed that the tumor cells were of donor origin. One year after the surgery, the patient is alive and has no evidence of tumor recurrence. Regardless of whether a kidney transplant is functioning, it should periodically be imaged for RCC throughout the recipient’s lifetime. In our experience, ultrasonography or CT with intravenous contrast is better than CT without contrast for the detection of tumor in a nonfunctioning kidney transplant.